2019
DOI: 10.1039/c9cc07777d
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous-oxidant- and catalyst-free electrochemical deoxygenative C2 sulfonylation of quinoline N-oxides

Abstract: By employing quinoline N-oxides as the starting materials, the electrochemical C–H sulfonylation of electron-deficient quinolines was indirectly achieved at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 55 publications
0
49
0
1
Order By: Relevance
“…For isoquinoline‐ N ‐oxide, formation of two regioisomers with a sulfo group at the 1 st or 3 d position in the ratio 1.1:1 was observed [206] . Electrochemical version of quinoline‐ N ‐oxides sulfonylation was also reported [207] . When sulfonyl hydrazides 373 were used as sulfonylation reagents, 2‐sulfonylated derivatives of quinolines 374 were synthesized from the corresponding N ‐oxides 372 using the I 2 /H 2 O 2 /NaOH [208] (Scheme 163a) or NaI/TBHP [209] (Scheme 163b) systems.…”
Section: Sulfonylation Of Heterocyclesmentioning
confidence: 95%
See 1 more Smart Citation
“…For isoquinoline‐ N ‐oxide, formation of two regioisomers with a sulfo group at the 1 st or 3 d position in the ratio 1.1:1 was observed [206] . Electrochemical version of quinoline‐ N ‐oxides sulfonylation was also reported [207] . When sulfonyl hydrazides 373 were used as sulfonylation reagents, 2‐sulfonylated derivatives of quinolines 374 were synthesized from the corresponding N ‐oxides 372 using the I 2 /H 2 O 2 /NaOH [208] (Scheme 163a) or NaI/TBHP [209] (Scheme 163b) systems.…”
Section: Sulfonylation Of Heterocyclesmentioning
confidence: 95%
“…[206] Electrochemical version of quinoline-N-oxides sulfonylation was also reported. [207] When sulfonyl hydrazides 373 were used as sulfonylation reagents, 2-sulfonylated derivatives of quinolines 374 were synthesized from the corresponding N-oxides 372 using the I 2 /H 2 O 2 / NaOH [208] (Scheme 163a) or NaI/TBHP [209] (Scheme 163b) systems. Similar results were obtained for isoquinolines and pyridines.…”
Section: Sulfonylation Of Six-membered Heterocyclesmentioning
confidence: 99%
“…One application of this technology is exemplified by Lei's sulfonylation of quinoline N ‐oxides using sodium sulfinates via a Minisci‐type mechanism (Scheme 53). [78] Sodium sulfinates 142 act as both the sulfonylation source and the activating agent.…”
Section: Simple C2‐h‐functionalizationmentioning
confidence: 99%
“…An iron (III)‐catalyzed protocol towards 2‐sulfonyl quinolines from quinoline N‐oxides and sodium sulfinates was illustrated by An group in the same year [46] . In 2019, the electrochemical deoxygenative C2 sulfonylation of quinoline N‐oxides with sodium sulfinates for the synthesis of sulfonylated quinoline derivatives was developed by Lei group [47] . Control experiments suggested that quinoline might not be a reaction intermediate.…”
Section: Sulfonylation Reaction Using Sodium Sulfinatesmentioning
confidence: 99%
“…[46] In 2019, the electrochemical deoxygenative C2 sulfonylation of quinoline N-oxides with sodium sulfinates for the synthesis of sulfonylated quinoline derivatives was developed by Lei group. [47] Control experiments suggested that quinoline might not be a reaction intermediate. Sulfonyl radical which was generated from the anodic oxidation of benzene sulfinate was proposed for this reaction (Scheme 37).…”
Section: Sulfonylation With Arenesmentioning
confidence: 99%